Spectrophotometric Method for the Estimation of Ceftriaxone in Pure Form and Pharmaceuticals - Ahmed, Aya W.; Al-Ameri, Salam A.H. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2020)
Ceftriaxone sodium were one of the widely antibacterial drugs used. Azo dye derivatization of diazonium salt that formed via the reaction between ceftriaxone with hydrochloric acid and sodium nitrite was developed for the on-research drug analysis then coupling with each one 2,5-dimethylphenol (2,5-DMP) and 4-tertbutylphenol (4-TBP) respectively in the alkaline media. The developed diazonium coupling methods include an optimization study. The results show a limit of detection and limit of quantification 0.482, 0.284 µg/mL, and 1.607, 0.945 µg/mL using 2,5-DMP and 4-TBP reagents respectively. Moreover, the recovery % obtained was 100.89%, and 103.37% at linear concentration range 3.0 – 50, and 10 – 30 µg/mL, with molar absorptivity of 4.377×103, 7.446×103 L. mol-1. cm-1 using 2,5-DMP and 4-TBP reagents respectively. An acceptable accuracy represented by the relative standard deviation (RSD%) was achieved of a 0.46 and 0.37 for 2,5-DMP and 4-TBP respectively. The proposed method was successfully used for the determination of ceftriaxone sodium in pure and in pharmaceuticals.